Stock Return Volatility and Financial Distress: Ownership Effects - Affan Fardan Navandra; Rahmat Setiawan (Universitas Prasetiya Mulya, 2025)
This study aims to analyze the effect of stock return volatility on financial distress moderated by corporate ownership structure. The study uses data from 1,007 observations involving six regression models that include various independent variables, including total asset turnover, net profit margin, profitability, audited firm, as well as moderating variables such as state ownership, foreign ownership, institutional ownership, and blockholders ownership. The results showed that stock return volatility has a positive significant effect on financial distress. Moderating variables provide mixed results, where state, foreign, and blockholders strengthen the positive relationship between stock return volatility and financial distress, while institutional ownership has a weakening effect. This study provides implications for corporate management in mitigating financial risk by ownership structure as part of the corporate governance strategy.